Growth and Impact of S&T Research in Madhya Pradesh during 2000-2009 - Sagar, Anil; Kademani, B.S. (DESIDOC Journal of Library & Information Technology, 2010)
The paper discusses the scientific contribution from Madhya Pradesh (India) as per the Web of Scienceexpanded version during 2000-2009. The parameters studied include growth of publications and citations, international collaborations, national collaborations, subject-wise distribution of publications, citations, activity index and collaboration rate, ranking of research and academic institutions, authorship and collaboration patterns, channels of communications, and major journals preferred by scientists of Madhya Pradesh for publishing their research works. http://dx.doi.org/10.14429/djlit.31.1.757